Calcifying characteristics of peripheral vascular smooth muscle cells of chronic kidney disease patients with critical limb ischemia. (April 2021) - Lee, Dong-Oh; Kim, Ji Hye; Kang, Ho Won; Kim, Dae Yoo; Lee, Wonik; Cho, Tae-Joon; Lee, Dong Yeon
The role of vascular smooth muscle cells (VSMCs) in vascular calcification, which is related to chronic kidney disease (CKD), has been studied in greater detail in the major arteries relative to the peripheral arteries. We compared the calcifying characteristics of peripheral VSMCs relative to non-pathologic major VSMCs in patients with severe peripheral artery disease (PAD). We isolated peripheral VSMCs from the posterior tibial artery of 10 patients with CKD who underwent below-knee amputation for critical limb ischemia (CLI). Using normal human aortic VSMCs as a control group, we cultured the cells in normal and high phosphate media for 10 days, and subsequently tested by immunofluorescence staining. We compared the calcification levels between the two groups using various assays, tests for cell viability, and scanning electron microscopy. As a result, calcification of pathologic peripheral VSMCs increased significantly with time ( p = 0.028) and was significantly higher than that in human aortic VSMCs in calcium assays ( p = 0.043). Dead cells in the pathologic VSMC group were more distinct in high phosphate media than in human aortic VSMCs. In conclusion, VSMCs from the peripheral artery of patients with severe CKD and CLI who underwent amputation surgery showed marked calcifying characteristics compared to normal human aortic VSMCs.